2013
DOI: 10.1189/jlb.1212660
|View full text |Cite
|
Sign up to set email alerts
|

Human scavenger protein AIM increases foam cell formation and CD36-mediated oxLDL uptake

Abstract: AIM is expressed by macrophages in response to agonists of the nuclear receptors LXR/RXR. In mice, it acts as an atherogenic factor by protecting macrophages from the apoptotic effects of oxidized lipids. In humans, it is detected in atherosclerotic lesions, but no role related to atherosclerosis has been reported. This study aimed to investigate whether the role of hAIM extends beyond inhibiting oxidized lipid-induced apoptosis. To accomplish this goal, functional analysis with human monocytic THP1 cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 55 publications
6
64
0
2
Order By: Relevance
“…We analyzed the CD36 receptor because of previous evidence that links the activity of these 2 molecules. 24,26 Flow cytometry analysis showed that CD5L induced higher MF cell surface expression of CD36, as previously observed. 26 Interestingly, in THP1-Vector MF, silencing of CD36 alone did not alter autophagy markers, which were almost absent, suggesting that this receptor does not modulate autophagy in basal conditions.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…We analyzed the CD36 receptor because of previous evidence that links the activity of these 2 molecules. 24,26 Flow cytometry analysis showed that CD5L induced higher MF cell surface expression of CD36, as previously observed. 26 Interestingly, in THP1-Vector MF, silencing of CD36 alone did not alter autophagy markers, which were almost absent, suggesting that this receptor does not modulate autophagy in basal conditions.…”
Section: Discussionsupporting
confidence: 60%
“…24,26 Flow cytometry analysis showed that CD5L induced higher MF cell surface expression of CD36, as previously observed. 26 Interestingly, in THP1-Vector MF, silencing of CD36 alone did not alter autophagy markers, which were almost absent, suggesting that this receptor does not modulate autophagy in basal conditions. In contrast, the reduction in CD36 cell surface receptor availability in CD5L-expressing MF lowered CD5L-induced LC3 puncta formation and LC3-LysoTracker Red colocalization.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations